Determinant factors of citizens' satisfaction with municipal services: the case of municipalities on the Island of São Nicolau - Nogueira, Sónia P. (2021)
This study aimed to find out residents' degree of satisfaction with local public services provided by local authorities. It also intended to identify the determinants of citizens' satisfaction. The research adopted a quantitative approach, through the application of a questionnaire survey to residents in the municipalities of Sao Nicolau in Cape Verde. Globally, citizens are satisfied with the municipality where they live. For the variables of Global Satisfaction with the municipality of residence and Global Satisfaction with the financial management of the local authority, there are no differences by the municipality of residence regarding citizens' satisfaction. As both are located on the island of Sao Nicolau, in principle, there should be no discrepancy in their form of action due to characteristics associated with insularity. Citizens' satisfaction is influenced positively by the Image of the Municipality, Quality of Basic Infrastructure and Services and Quality of Life in Leisure, Access to Culture, Environmental Quality and Safety. Quality in Economic Terms, on the other hand, seems to have not influenced the citizen's satisfaction.